Hubungan Tingkat Kebugaran Dengan Konsentrasi Pembelajaran Pendidikan Jasmani Pada Peserta Didik - Farhan Hafidz Sidik; Nurwansyah, Rhama; Purbangkara, Tedi (Jurnal Porkes, 2024)
This study aims to show the relationship between physical fitness level and physical education learning concentration. The population of this study were all students of class VIII of Al Amin Islamic Junior High School, North Cikarang. By using the cluster random sampling technique, one class from the total VIII class was selected as the sample to be studied. This research is a quantitative research with correlational method. The data used is data obtained from instruments in the form of an Indonesian student fitness test to measure the level of physical fitness of students and a concentration grid test to measure the level of concentration of students. To prove the hypothesis proposed, the data analysis used is a simple linear regression analysis technique. Based on the results of the study, it was found that there was a relationship between the level of physical fitness on the concentration of students, namely r count (0.432) > r table (0.349) at alpha = 5% with N = 31-1 = 30 and a significance value of p 0.015 < 0.05. These results are positive, meaning that the better the physical fitness, the better the concentration of students. The result of the coefficient of determination (r2) obtained of 0.186 means that physical fitness contributes 18.60% to the concentration of students' learning, and the remaining 81.40% is influenced by other factors.